2012
DOI: 10.1017/s002210901200049x
|View full text |Cite
|
Sign up to set email alerts
|

Information Content of Earnings Announcements: Evidence from After-Hours Trading

Abstract: We study after-hours trading (AHT), price contributions, and price discovery following quarterly earnings announcements released outside of the normal trading hours. For Standard & Poor's (S&P) 500 index stocks from 2004-2008, AHT is heightened on announcement days. A significant portion of the price change and price discovery occurs immediately after the earnings releases. Prices in AHT show a large degree of informational efficiency, further demonstrating the importance of price discovery in AHT. We also pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
37
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 46 publications
12
37
1
Order By: Relevance
“…It is likely that noise trading is one of the causes of this increased AMC liquidity. Whereas Jiang et al (2012) find that AMC announcements lead to more price discovery during after-hours trading, we document that AMC announcements have a differential effect on liquidity when the market opens on the following day.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…It is likely that noise trading is one of the causes of this increased AMC liquidity. Whereas Jiang et al (2012) find that AMC announcements lead to more price discovery during after-hours trading, we document that AMC announcements have a differential effect on liquidity when the market opens on the following day.…”
Section: Discussioncontrasting
confidence: 80%
“…Since noise-trader behavior is a primary focus of our paper, we choose to examine trading activity during regular market hours in order to capture noise-trader effects. We suggest that our results complement those of Jiang et al (2012) since multiple factors may help to contribute to managers' decisions to announce AMC.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Michaely et al (2014) show that five percent of earnings are reported during RTHs in 2002, down sharply from the 45% of earnings announcements made during RTHs in the late 1990s. Jiang et al (2012) use this decline in RTH announcements to motivate a study about when investors trade (before the market opens or after the market closes) and how investors contribute to price discovery following earnings announcements. Jiang et al (2012) show that trading volume increases on announcement days, and also document a smaller average trade size during the before and after market trading sessions.…”
Section: Related Literaturementioning
confidence: 99%
“…Current research on HFTs focuses primarily on regular trading hours (RTHs), but not on trading before the market opens or after the market closes. Jiang et al (2012) show that most earnings announcement are made after the market closes. In addition, they show a significant portion of the price change and price discovery occurs after earnings releases, both in the period prior to the market opening and in the after-hours trading sessions.…”
Section: Introductionmentioning
confidence: 99%